Development of a Wizer.me Assisted Chemo-Entrepreneurship Based e-Worksheet on Freezing Point Depression Oriented Toward Students Creativity - valina valina; Haryanto Haryanto; Afrida Afrida; Epinur Epinur; Firdiawan Ekaputra; Febbry Romundza (SAINTIFIK@: Jurnal Pendidikan MIPA, 2026)
This study aims to find out the process of developing teaching materials, the level of conceptual feasibility based on the assessment of material experts, media experts, teacher assessments and student responses to e-LKPD of chemo-entrepreneurship-based  frozen point reduction material assisted wizer.me creativity-oriented. This research is a development research using the Lee & Owens model. The instruments used in this study include interview guidelines, student needs questionnaires, expert validation sheets, teacher assessment sheets, and student response questionnaires. The analysis techniques used are qualitative and quantitative data analysis, the results are validated by material experts and media experts. The results of the study show that the e-LKPD developed has met the feasibility criteria conceptually and procedurally. The validation of material experts obtained an average score of 4.58 or 91.6% (very feasible), the validation of media experts of 4.62 or 92.4% (very feasible), and the teacher's assessment of 4.56 or 91.2% (very feasible). The product trials were carried out through small group trials, each of which obtained a response percentage of 89.4% with the very good category. Based on the results obtained, it can be concluded that the e-LKPD of chemo-entrepreneurship-assisted  wizer.me creativity-oriented frozen point reduction material developed is declared feasible and very good for use in the chemistry learning process, especially frozen point reduction material. This media is able to help students understand the material contextually and the learning atmosphere is more interesting.